Absolute Psoriasis Area and Severity Index as a valuable marker to determine initial treatment response in psoriasis patients treated with guselkumab in routine clinical care. Issue 1 (25th November 2021) - Seidl, Ulrich; Pinter, Andreas; Wilsmann‐Theis, Dagmar; Poortinga, Sietske; Morrison, Kirsten; Mrowietz, Ulrich; Gerdes, Sascha
Abstract: Guselkumab is an anti‐interleukin‐23p19 monoclonal antibody approved as a first‐line medication in patients with moderate‐to‐severe plaque‐type psoriasis and second‐line in active psoriatic arthritis. In the clinic, patients who have shown a lack of previous treatment efficacy and/or tolerability are often prescribed guselkumab. These patients generally have less severe psoriasis compared to clinical trial cohorts, reflected in lower Psoriasis Area and Severity Index (PASI). To evaluate treatment response in a real‐world setting, we conducted a multicenter‐retrospective chart review in three specialized dermatological centers. Seventy‐four patients who received guselkumab treatment were included in the study and baseline characteristics were described. The mean PASI at baseline was 13.0 (± 6.7). After 12 weeks of treatment 40 patients could be followed up at the participating centers and efficacy was assessed: 72.5% of these patients achieved an absolute PASI ≤5 (55.0% ≤3; 42.5% ≤2) whereas only 57.5% of patients were able to gain a delta PASI reduction of at least 75%. Using the absolute PASI as a treatment goal rather than response rate revealed that guselkumab was highly effective in this real‐world setting. In conclusion, the absolute PASI proved to be a more valuable tool to measure treatment outcome.